Concept Attainment in Mathematics and Its Predictors - Upadhyay, Sunil Kumar (INDIAN EDUCATIONAL REVIEW, 2019)
Mathematics is an important subject of school curriculum because it is a science which draws necessary conclusions for cultivating our civilizations and developing intellectual values in human being. Mathematics is full of concepts. Basic to mathematics learning is the attainment of mathematical concepts. Without attaining concepts in mathematics, mathematical success cannot be achieved. The present study was designed to find the contribution of logical reasoning, mathematical creativity, socio-economic status and concept attainment model on attainment of mathematical concepts. The findings of present study show the predictive efficiency and contribution of predictors on attainment of concepts in mathematics.